The administration sequences of immune checkpoint inhibitors and chemotherapy cause discrete efficacy when treating non-small cell lung cancer: a retrospective study - Zhang, Bicheng; Song, Yuxiao; Min, Qian; Cheng, Weiting; Wang, Jun; Fu, Yang; Yin, Jiaxin (Frontiers in Immunology, 2025)
BackgroundImmune checkpoint inhibitors (ICIs) combined with chemotherapy have become a standard first-line treatment for advanced non-small cell lung cancer (NSCLC). However, the optimal sequence of administrating the two treatments remains controversial.MethodsThis study included advanced NSCLC patients who received ICIs combined with chemotherapy at Renmin Hospital of Wuhan University and Xiangyang Hospital, Hubei University of Chinese Medicine between 1st September 2020 and 30th September 2024. Patients were categorized into the concurrent, immune-chemo, and chemo-immune groups based on different sequences of treatment administration. The primary endpoints evaluated were survival and treatment efficacy. The secondary endpoint assessed was treatment-related adverse events (TRAEs).ResultsThis two-center, retrospective study included 270 NSCLC patients who received ICIs plus chemotherapy. Survival analysis revealed statistically significant differences across treatment groups. The median overall survival (mOS) durations were 636 days (concurrent group), 615 days (immune-chemo group), and 749 days (chemo-immune group), with a log-rank test demonstrating significant intergroup differences (P = 0.0017). Similarly, median progression-free survival (mPFS) showed distinct patterns at 178 days, 180 days, and 216 days for the respective groups (log-rank P = 0.0134). Additionally, the objective response rates (ORRs) for the three groups were 55.82% (72/129), 58.21% (39/67), and 68.92% (51/74), respectively. The incidence of TRAEs of any grade in the concurrent, the immune-chemo, and the chemo-immune groups was 77.52% (100/129), 65.67% (44/67), and 59.46% (44/74) rates, respectively, which was a significant difference (χ²=7.91, P=0.019). Despite patients experiencing Grade 3 or higher TRAEs had extremely poor prognoses, overall, patients who developed any grade of TRAEs had better survival outcomes, particularly those with skin or endocrine toxicity.ConclusionsThese findings suggest that the administration sequence of chemotherapy followed by ICIs may yield the greatest clinical benefit, providing a basis for clinical decision-making.